MODELLING OF REINFORCED CONCRETE COUPLING BEAMS WITH HEADED BARS: VERIFICATION AND PARAMETRIC STUDIES - Tambusay, Asdam; Krisnajana, Joshua F; Suryanto, Benny; Suprobo, Priyo (Institut Teknologi Sepuluh Nopember, 2023)
This paper explores the accuracy of nonlinear finite element procedures implemented in ATENA in predicting the load-drift response of reinforced concrete coupling beam with headed bars under reversed cyclic loading. In this study, one of the coupling beams incorporating headed bars, tested by Seo and co-workers in 2017, is analysed and its response at different lateral drifts is discussed. Parametric analyses, studying the influence of reinforcement layouts, are also presented. It is shown that the hysteresis loops of the coupling beam could be predicted accurately, along with the crack patterns at different stages of loading and failure mode. It is also shown that the omittance of headed bars resulted in more pronounced bond-slip effects and a more severe pinched response in the post-peak region, highlighting the importance of providing adequate headed reinforcement. A similar trend was observed in the coupling beam with the omittance of U-bars and horizontal transverse reinforcements, whereas stirrup relaxation was found to increase the prominence of shear failure.